Towards a medication core data set for the medical Informatics Initiative (MII): Initial mapping experience between the German procedure classification (OPS) and the identification of medicinal products (IDMP) - Zabka, Susanne; Ammon, Danny; Ganslandt, Thomas; Gewehr, Jan; Haverkamp, Christian; Kiefer, Saskia; Lautenbacher, Heinrich; Löbe, Matthias; Thun, Sylvia; Boeker, Martin (CEUR Workshop Proceedings, 2019)
Documentation of medication processes is among the most difficult tasks associated with digital clinical documentation. Despite its great potential medical impact, it has not been consistently adopted in German university hospitals, with one of the reasons being the lack of a comprehensive information model with sound terminological support. With the Identification of Medicinal Products (IDMP), several international authorities have recently provided a comprehensive set of standards for the formal description of drugs, mainly for regulatory purposes. In this paper, we describe the approach of the German Medical Informatics Initiative (MII) towards the modelling of a medication core dataset using IDMP. Three different process models with minimal datasets for medication were defined: summative documentation of episodes, point-wise documentation, and medication plans (snapshot documentation). As a feasibility study evaluating how standard terminologies can be used for a minimal data set of hospital medication data, a mapping between IDMP terminologies and the medication chapter of the German Procedure Classification “OPS” (Operationenund Prozedurenschlüssel) was developed. About 1700 OPS classes, representing about 160 highly reimbursement relevant drugs, were mapped onto different axes of IDMP (substances, optionally: routes of administration and units) using several coding systems with different scopes, to analyze their coverage and particular advantages. A mapping was possible for almost all OPS codes. For the substances, it is necessary to distinguish between the common substance name and the active ingredient, as these may be different for a drug. This “lightweight” mapping approach demonstrates the basic feasibility of using IDMP for medication documentation.
CRIS-Team Scopus Importer:2021-11-16
Keywords: Data standards; German Medical Informatics Initiative; Identification of Medicinal Products (IDMP); Medication data; Standards mapping; Terminology